The Influence Of The Work Environment On Employee Comfort Using The Method Failure Mode And Effect Analysis (FMEA) - Hanan Almeyda Hanesa; Endro Prihastono (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Employee performance is a very influential factor in the work system. Therefore, to reduce the wrong side of employee performance, it is necessary to have employee comfort and a work environment to improve a company’s quality and optimal performance. This study aims to analyze the effect of employee comfort and work environment on employee performance (at PT. Danwood Nusantara) using the methodFMEA (Failure Mode and Effect Analysis). The types of data used are primary data and secondary data. Data processing using the FMEA method, fishbone diagrams and productivity level calculations. The study results show that from the data obtained through interviews, three variables have a small value (must be corrected): comfort with lighting, room temperature, and noise. Data processing using the Results Analysis method Failure Mode and Effect Analysis (FMEA) shows that three types of work accidents have high RPN values: cutter scratches, pinched storage racks, and sprains when lifting goods. The productivity level in the warehouse is 0.99741 of the 16688 working hours that should have been lost due to work accidents 43 hours 10 minutes. The impact of work accidents can reduce employee productivity, thereby indirectly harming the company